2021
DOI: 10.1111/ijac.13972
|View full text |Cite
|
Sign up to set email alerts
|

Wettability and interfacial phenomena in the liquid‐phase bonding of refractory diboride ceramics: Recent developments

Abstract: Joining and integration technologies are integral to manufacturing of components based on ultrahigh-temperature ceramics (UHTCs) such as transition metal diborides. Brazing is a particularly attractive joining technique because of its simplicity and versatility, but its use to join the UHTCs demands knowledge of the complex interplay among high-temperature wettability, interfacial reactions, and chemical and thermoelastic compatibilities. This paper summarizes the research and development activities carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The microstructure and elemental analysis of the matrix material are depicted in Figure 2. The results indicated that the LM26 alloy had better wettability between all types of ceramics reinforced within it [3]. By optimizing the distribution and dispersion of ceramic particles in the matrix, the mechanical properties of the composite are improved.…”
Section: Selection Of Matrix Alloy and Ni-gr Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The microstructure and elemental analysis of the matrix material are depicted in Figure 2. The results indicated that the LM26 alloy had better wettability between all types of ceramics reinforced within it [3]. By optimizing the distribution and dispersion of ceramic particles in the matrix, the mechanical properties of the composite are improved.…”
Section: Selection Of Matrix Alloy and Ni-gr Contentmentioning
confidence: 99%
“…Composite materials, known as metal matrix composites (MMCs), are created by combining a matrix material, such as aluminum, titanium, magnesium, or copper, with reinforcement materials, such as carbides, metallic oxides, borides, nitrides, or non-metallic materials such as red mud or fly ash [1][2][3][4]. The reinforcement materials are dispersed throughout the matrix and provide improved properties over the matrix alone, and slower degradation than the reinforcement materials alone.…”
Section: Introductionmentioning
confidence: 99%
“…Joining these dissimilar materials is difficult and technologies currently used are complex and relatively costly. According to Asthana and Sobczak [3] coating-substrate adhesion is promoted by wettability and develops physical, chemical and mechanical interactions. Chemical reactions at the surface are especially difficult to achieve for ceramic materials, due to their strong ionic-covalent bonding types (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Wettability in high-temperature solid-liquid systems is supported by such interactions as dissociation of surface oxides on the liquid metal, chemical dissolution of the solid in the melt, adsorption of reactive solutes and formation of an interfacial compound [6]. Metallic, ionic or covalent bonds are formed and the most desirable are interfacial metallic bonds, which provide more ductile high-strength composites [2].…”
Section: Introductionmentioning
confidence: 99%

Archives of Foundry Engineering

Hosadyna-Kondracka,
Nowak,
Turalska
et al. 2022